السياسة الروسية تجاه إفريقيا: العلاقات الجزائرية الروسية أنموذجا (1992 – 2022) Page de garde, sommaire et éditorial - بن الشيخ ., عصام (University of Eloued جامعة الوادي, 2023)
السياسة الروسية تجاه إفريقيا: العلاقات الجزائرية الروسية أنموذجا (1992 – 2022) Russian policy towards Africa: Algerian-Russian relations as a model (1992 – 2022) ***************************************************** الملخص: تأسست العلاقات الجزائرية الروسية منذ بداية النصف الثاني من القرن 20 الماضي، وتعززت أكثر مطلع القرن 21 حيث لم تقطع الجزائر علاقاتها مع موسكو بعد تفكك الاتحاد السوفييتي السابق عام 1991، ويعتبر التعاون الدبلوماسي والعسكري والطاقوي أهمّ مجالات التعاون الثنائي بين البلدين، كما تستفيد الجزائر من فرص التعاون الروسي متعدّد الأطراف مع دول القارة الإفريقية، بما يتيح لها استغلالا كاملا لمحدّدات قواتها لتفعيل الدور الجزائري في المسرح الدولي، وبعد الحرب الروسية على أوكرانيا في (فبراير 2022) بقيت العلاقات الجزائرية الروسية في مستوى جيّد أثبتته الدبلوماسية الجزائرية في المحافل الدولية. الكلمات المفتاحية: الجزائر، روسيا، التسلح، الطاقة، الشراكة، التعاون، التبعية، الهيمنة، التنمية، السيادة ********************************** The Abstrat: Algerian-Russian relations were established since the beginning of the second half of the last 20th century, and were further strengthened at the beginning of the 21st century, as Algeria did not cut its relations with Moscow after the dissolution of the former Soviet Union in 1991. Diplomatic, military and energy cooperation is considered the most important areas of bilateral cooperation between the two countries. Algeria also benefits from opportunities Russian multilateral cooperation with the countries of the African continent, allowing them to make full use of the limitations of their forces to activate the Algerian role in the international scene, and after the Russian war on Ukraine (February 2022), Algerian-Russian relations remained at a good level, which was proven by Algerian diplomacy in international forums. Keywords: Algeria, Russia, armaments, energy, partnership, cooperation, dependency, hegemony, development, sovereignty
المجلد 14 العدد1
Keywords: جزائر، روسيا، التسلح، الطاقة، الشراكة، التعاون، التبعية، الهيمنة، التنمية، السيادة; Algeria, Russia, armaments, energy, partnership, cooperation, dependency, hegemony, development, sovereignty